2019
DOI: 10.1021/acsomega.9b01761
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of the Properties of Direct-Current Magnetron-Sputtered Al-Doped ZnO Polycrystalline Films Containing Retained Ar Atoms Using 10-nm-Thick Buffer Layers

Abstract: The use of a 10-nm-thick buffer layer enabled tailoring of the characteristics, such as film deposition and structural and electrical properties, of magnetron-sputtered Al-doped ZnO (AZO) films containing unintentionally retained Ar atoms. The AZO films were deposited on glass substrates coated with the buffer layer via direct-current magnetron sputtering using Ar gas, a substrate temperature of 200 °C, and sintered AZO targets with an Al2O3 content of 2.0 wt %. The use of a Ga-doped ZnO film possessing a text… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 73 publications
0
11
0
Order By: Relevance
“…Sputtering is a widely used method for fabricating ZnO thin films as it enables controllable composition and large-scale deposition. Single-phase hexagonal ZnO is obtained with optimized parameters. An X-ray diffraction peak is observed at 34°, which corresponds to the (002) orientation of ZnO .…”
Section: Fabrication Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sputtering is a widely used method for fabricating ZnO thin films as it enables controllable composition and large-scale deposition. Single-phase hexagonal ZnO is obtained with optimized parameters. An X-ray diffraction peak is observed at 34°, which corresponds to the (002) orientation of ZnO .…”
Section: Fabrication Methodsmentioning
confidence: 99%
“…The AZO thin films deposited at 300 and 350 °C exhibited much higher electrical stability than those prepared at lower substrate temperatures after 30 min of annealing at 400 °C in ambient air. Moreover, Nomoto et al reported that AZO deposited via DC sputtering with a thin buffer layer showed effective enhancement in the c -plane orientation and carrier transport properties . Adatoms with excess free energy on the deposition surface can be incorporated into the buffer layer during deposition.…”
Section: Fabrication Methodsmentioning
confidence: 99%
“…As seen ZnO oxygen vacancy by photoluminescence spectroscopy in ZnO, the positive association between the Sample content of polar faces and the surface oxygen vacancy will definitely serve a possible well trap one or two electrons to support the electron hole dividing, thus, higher photo-catalytic activities. The most high-aspect particles often have the least photo-catalytic action, photocatalytic variations have been found between the various particle sizes, and the dominant type effect tends obscure size effect [29]. ZnO structure pressure from little nickel raises the efficiency of photodegradation but the further rise of the dopant concentration results in a reduction in the Particle size of photocatalyst action the surface area has a direct impact on the photocatalyst's photocatalyst activities.…”
Section: Morphology Dependent Photocatalytic Activity Of Znomentioning
confidence: 99%
“…Most of the technique’s require either high substrate temperature or thermal post-treatment to prepare AZO thin films with high figures of merit (FOM). Of the above processes, direct current (DC) magnetron sputtering 16 is an industrially acceptable technique. It can produce highly transparent conductive thin films with good scalability on a large area with a faster deposition rate.…”
Section: Introductionmentioning
confidence: 99%